Low-frequency cortical responses to natural speech reflect probabilistic phonotactics - Di Liberto, Giovanni M.; Wong, Daniel; Melnik, Gerda Ana; de Cheveigné, Alain (NeuroImage (Orlando, Fla.), 2019)
Humans comprehend speech despite the various challenges such as mispronunciation and noisy environments. Our auditory system is robust to these thanks to the integration of the sensory input with prior knowledge and expectations built on language-specific regularities. One such regularity regards the permissible phoneme sequences, which determine the likelihood that a word belongs to a given language (phonotactic probability; “blick” is more likely to be an English word than “bnick”). Previous research demonstrated that violations of these rules modulate brain-evoked responses. However, several fundamental questions remain unresolved, especially regarding the neural encoding and integration strategy of phonotactics in naturalistic conditions, when there are no (or few) violations. Here, we used linear modelling to assess the influence of phonotactic probabilities on the brain responses to narrative speech measured with non-invasive EEG. We found that the relationship between continuous speech and EEG responses is best described when the stimulus descriptor includes phonotactic probabilities. This indicates that low-frequency cortical signals (<9 Hz) reflect the integration of phonotactic information during natural speech perception, providing us with a measure of phonotactic processing at the individual subject-level. Furthermore, phonotactics-related signals showed the strongest speech-EEG interactions at latencies of 100–500 ms, supporting a pre-lexical role of phonotactic information.